CPC-012 An Italian Cost-Effectiveness Analysis of Paclitaxel Albumin (Nab-Paclitaxel) Vs. Conventional Paclitaxel For Metastatic Breast Cancer Patients: The COSTANZA Study. (12th March 2013) - Lazzaro, C; Bordonaro, R; Cognetti, F; Fabi, A; De Placido, S; Arpino, G; Marchetti, P; Botticelli, A; Pronzato, P; Martelli, E
Abstract : Background: Paclitaxel albumin (nab-paclitaxel) is a nanoparticle albumin-bound paclitaxel formulated with the aim of increasing the therapeutic index in metastatic breast cancer (MBC). When compared to conventional paclitaxel, nab-paclitaxel has reported longer time to progression, higher response and overall survival, lower incidence of neutropenia, no need for premedication and a shorter time of administration. Purpose: To investigate nab-paclitaxel's cost effectiveness vs. conventional paclitaxel for MBC patients in Italy. Materials and Methods: A Markov model with progression-free, progressed, and dead states was developed to estimate costs, outcomes and quality-adjusted life-years (QALYs) over 5 years from the Italian National Health Service (INHS) viewpoint. Patients were assumed to receive nab-paclitaxel 260 mg/m² 3-weekly (q3w) or conventional paclitaxel 175 mg/m² q3w. Data on health care resources consumption was collected from a survey performed on five Italian centres. Resources were valued at Euro (€) 2011. Published utility weights were applied to health states to estimate the impact of response, disease progression and adverse events on QALYs. Three sensitivity analyses tested the robustness of the base case incremental cost-effectiveness ratio (ICER). Results: Compared to conventional paclitaxel, nab-paclitaxel gains an extra 0.165 QALYs (0.265 life-years saved) and incurs additional costs of €2505 per patient treated. This translates to an ICER of €15, 189 (95%CI: €11, 891; €28, 415). One-way sensitivity analysis confirms the stability of the ICER for nab-paclitaxel despite the variations in the cost of taxanes. Threshold analysis shows that the ICER for nab-paclitaxel exceeds €40, 000 only if cost per mg of conventional paclitaxel is set to zero. Probabilistic sensitivity analysis highlighted that nab-paclitaxel has a 0.99 probability of being cost effective for a threshold value of €40, 000 and is the optimal alternative from a threshold value of €16, 316 onwards. Conclusions: Based on those findings, nab-paclitaxel can be considered highly cost effective when compared to the acceptability range for ICERs proposed by the Italian Health Economics Association (€25, 000;€40, 000) No conflict of interest.